2023
DOI: 10.1186/s13018-023-04093-w
|View full text |Cite
|
Sign up to set email alerts
|

Combination of percutaneous endoscopic lumbar discectomy and platelet-rich plasma hydrogel injection for the treatment of lumbar disc herniation

Lidong Zhang,
Chengliang Zhang,
Dajiang Song
et al.

Abstract: Objective To determine the safety and efficacy of percutaneous endoscopic lumbar discectomy (PELD) combined with platelet-rich plasma (PRP) hydrogel injection in patients with lumbar disc herniation (LDH). Methods A total of 98 consecutive patients with LDH who underwent either PELD combined with PRP hydrogel injection or PELD alone were reviewed. This retrospective study was performed between January 2019 and January 2021. Clinical outcomes were c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In terms of clinical research, Akeda et al [ 16 ] conducted an initial clinical trial in 2011, providing the first evidence that intra-disc application of autologous PRP is an effective treatment for degenerative disc diseases. Since then, numerous scholars have reported the application of PRP in alleviating back pain and neurogenic symptoms, with sustained long-term clinical effects [ 1 , 13 , 17 ]. In our study, patients treated with PRP injection demonstrated a greater advantage in terms of pain relief and neurological function improvement, aligning with the outcomes of previous trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of clinical research, Akeda et al [ 16 ] conducted an initial clinical trial in 2011, providing the first evidence that intra-disc application of autologous PRP is an effective treatment for degenerative disc diseases. Since then, numerous scholars have reported the application of PRP in alleviating back pain and neurogenic symptoms, with sustained long-term clinical effects [ 1 , 13 , 17 ]. In our study, patients treated with PRP injection demonstrated a greater advantage in terms of pain relief and neurological function improvement, aligning with the outcomes of previous trials.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) is a common spinal disease in clinical practice, showing a developing trend of low age and high incidence [ 1 ]. For patients with mild symptoms, conservative treatment can alleviate the symptoms, but surgical intervention is still required for patients who do not respond to conservative treatment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains higher levels of cytokines and growth factors that can promote angiogenesis, accelerate endothelial regeneration, stimulate tissue repair and healing processes, and increase collagen content in different types of tissues. [34][35][36][37][38] When platelets are activated in PRP, they can produce many growth factors, including platelet-derived growth factor, basic fibroblast growth factor, transforming growth factor-β, insulin-like growth factor, vascular endothelial growth factor, etc. They can promote the production of collagen II and chondrocytes, prevent apoptosis of mesenchymal stem cells and chondrocytes, and avert the catabolic effects of inflammatory cytokines like interleukin-1β and matrix metalloproteinase.…”
Section: Discussionmentioning
confidence: 99%